PERSPEKTIF AGRIBISNIS KAKAO DI SULAWESI TENGGARA (Studi kasus Kabupaten Kolaka) - VALERIANA DARWIS; NUR KHOIRIYAH AGUSTIN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
Disease-pest attack is extremely affected cocoa harvesting. This paper also study cocoaagribusiness in Kolaka District, South-East Sulawesi which focused on production, price,marketing and institution aspects. The result shows production reduced 40 – 50 percentbecause of disease-pest attack, there is no price differentiation on fermented cocoa andunfermented cocoa, price transformation faster received to farmer when cocoa price reduced,the farmers which near subdistrict market are more free to sell their cocoa, and the farmer lessaccess to inventory cooperative.